1988
DOI: 10.1115/1.3187837
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model for Convective Cooling During the Grinding Process

Abstract: Heat generated during grinding may cause thermal damage to the workpiece and wheel. To avoid this, grinding fluids are often used, but their effects are not well understood. A simple analytical model of the convective heat transfer between the wheel and workpiece surfaces and the grinding fluid is described. The model predicts the convective heat transfer coefficient at the workpiece surface, the fraction of energy entering the workpiece, and the workpiece surface temperature. Despite its simplicity, the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…1 Heat transfer paths among the fluid, grain and workpiece fluid is sufficient and the position of the nozzle is appropriate. It is also shown that the fluid can fill the pores within the entire thermal boundary layer, even in creep feed grinding [7]. Since the chip volume is small compared to the thermal boundary layer volume, the mixed properties of the fluid and the chip can be assumed to be the same as those of the pure fluid.…”
Section: Model Of Grinding Zonementioning
confidence: 99%
See 2 more Smart Citations
“…1 Heat transfer paths among the fluid, grain and workpiece fluid is sufficient and the position of the nozzle is appropriate. It is also shown that the fluid can fill the pores within the entire thermal boundary layer, even in creep feed grinding [7]. Since the chip volume is small compared to the thermal boundary layer volume, the mixed properties of the fluid and the chip can be assumed to be the same as those of the pure fluid.…”
Section: Model Of Grinding Zonementioning
confidence: 99%
“…Hann [3], Malkin and Anderson [4], Malkin [5], Rowe and Morgan [6] derived thermal partition and workpiece temperature in dry grinding that failed to take into account the cooling effect of the fluid. Lavine [7] conducted a simple thermal model by treating the wheel and the fluid as a ''composite solid.'' Lavine et al [8] presented a conical grain model, with grain slope set to one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to calculate ( ), which is defined as an integral in (22), consider this more general form of the same integral,…”
Section: Taylor Expansion Of the Integrandmentioning
confidence: 99%
“…Table 2 shows three sets of parameters (in SI units) for the numerical simulations. Data set 1 considers a carbon steel workpiece AISI 1020 [21] and data set 2 considers aluminum oxide, Al 2 O 3 (sapphire), as workpiece material [22]. Also, data set 3 considers a titanium alloy VT20 workpiece, whose thermal properties are given in [23].…”
Section: Characteristic Dimensionless Depthmentioning
confidence: 99%